2006
DOI: 10.2527/2006.843712x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors influencing heat stress in feedlot cattle1,2

Abstract: Data from 3 summer feedlot studies were utilized to determine the environmental factors that influence heat stress in cattle and also to determine wind speed (WSPD; mؒs −1 ) and solar radiation (RAD; Wؒm −2 ) adjustments to the temperature-humidity index (THI). Visual assessments of heat stress, based on panting scores (0 = no panting to 4 = severe panting), were collected from 1400 to 1700. Mean daily WSPD, black globe temperature at 1500, and minimums for nighttime WSPD, nighttime black globe THI, and daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
556
2
45

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 693 publications
(613 citation statements)
references
References 15 publications
10
556
2
45
Order By: Relevance
“…The variability was in the length of acclimation period and ranged from 9 days for Angus and Charolais to 14 days for Polled Hereford (Hereford and Santa Gertrudis had intermediate values (12 days)). In a recent study, Brown-Brandl et al (2006) reported a significant effect of breed and breed by temperature interaction on respiration rates and panting scores. Angus and MARC III breeds had the highest respiration rate and panting score, followed by Gelbvieh and then Charolais.…”
Section: Heat Stress Critical Temperatures and Bioclimatic Indicesmentioning
confidence: 96%
See 2 more Smart Citations
“…The variability was in the length of acclimation period and ranged from 9 days for Angus and Charolais to 14 days for Polled Hereford (Hereford and Santa Gertrudis had intermediate values (12 days)). In a recent study, Brown-Brandl et al (2006) reported a significant effect of breed and breed by temperature interaction on respiration rates and panting scores. Angus and MARC III breeds had the highest respiration rate and panting score, followed by Gelbvieh and then Charolais.…”
Section: Heat Stress Critical Temperatures and Bioclimatic Indicesmentioning
confidence: 96%
“…Beef cattle are particularly vulnerable not only to extreme environmental conditions but also to rapid changes in climate. In particular, fatter cattle (subcutaneous fat acts like insulation and slows heat dissipation), cattle with a heavy hair coat (more insulation) and darker-coated animals (black and dark red cattle) are very sensitive to heat (Brown-Brandl et al, 2006;Gaughan et al, 2009b). The Scientific Committee on Animal Figure 5 Effects of heat stress (HS) or pair-feeding (PF) on (a) dry matter intake and (b) milk yield in lactating Holstein cows.…”
Section: Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The panting score (PS) is an example of the latter and is based on visual evaluation of the presence and degree of two important heat stress signs in cattle, panting and drooling (Mader et al, 2006 andSchütz et al 2014). The score varies between 0 (no panting or drooling) and 4.5 (extreme panting and drooling).…”
Section: Introductionmentioning
confidence: 99%
“…Proactive planning of cattle handling and management based on weather-predictions, requires antecedent validation of climatic heat stress indices and associated heat stress thresholds (Table 1). Not all heat stress thresholds have been validated based on animal-based measures, but the more recent climatic indices, such as the heat load index (HLI; Gaughan et al, 2008), an adjusted version of the temperature humidity index (Mader et al, 2006) and the comprehensive climatic index (Mader et al, 2010) do have validated heat stress thresholds (Table 1). In addition, Gaughan et al (2010b) compared the tolerance to increasing HLI values, based on increasing PS, for several (n = 17 total) Bos indicus, Bos taurus and B. indicus × B. taurus feedlot steers, during summertime in Australia, which is characterised by a warm climate.…”
Section: Introductionmentioning
confidence: 99%